Digital Family Assistance & Mentoring (DFAM) to Enhance Exclusive Breastfeeding Practices among Young Mothers or Stunting Prevention” - Lintje Sintje Corputty; Wildia Nanlohy; Nova Bugis; Siti Nurhidayati; Abdul Thalib (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stunting remains a major public health problem in Indonesia, partly driven by low exclusive breastfeeding rates and limited family support. Digital Family Assistance & Mentoring (DFAM) was developed as a family-centered digital intervention to support exclusive breastfeeding as a stunting prevention strategy.This study aimed to examine the effectiveness of DFAM in improving knowledge, attitudes, exclusive breastfeeding practices, and family support among breastfeeding mothers. This quasi-experimental study used a pretest–posttest control group design and was conducted in Dobo, Aru Islands. A total of 70 breastfeeding mothers with infants aged 0–6 months were selected using purposive sampling and divided into an intervention group (n=35) and a control group (n=35). The intervention group received DFAM, while the control group received standard breastfeeding education. Data were collected using structured questionnaires. Instrument validity was tested using Pearson correlation and reliability using Cronbach’s alpha, with all instruments meeting acceptable criteria. Data were analyzed using the Wilcoxon Signed-Rank test (p < 0.05). Significant improvements were observed in the intervention group for attitudes (p = 0.040), exclusive breastfeeding practices (p = 0.002), and family support (p = 0.024), while knowledge improvement was not statistically significant (p = 0.120). The control group also showed significant improvements (p = 0.001), but with lower behavioral impact. DFAM is effective in improving exclusive breastfeeding practices by strengthening maternal attitudes and family support, indicating its potential as a digital, family-based strategy for stunting prevention.